Assessing the Influence of First Nation Education Counsellors on First Nation Post-secondary Students and Their Program Choices - Williamson, Pamela Margaret Elizabeth
The exploratory study focused on First Nation students and First Nation education counsellors within Ontario. Using an interpretative approach, the research sought to determine the relevance of the counsellors as a potentially influencing factor in the students’ post-secondary program choices. The ability of First Nation education counsellors to be influential is a consequence of their role since they administer Post-Secondary Student Support Program (PSSSP) funding. A report evaluating the program completed by Indian and Northern Affairs Canada in 2005 found that many First Nation students would not have been able to achieve post-secondary educational levels without PSSSP support. Eight self-selected First Nation Education counsellors and twenty-nine First Nation post-secondary students participated in paper surveys, and five students and one counsellor agreed to complete a follow-up interview. The quantitative and qualitative results revealed differences in the perceptions of the two survey groups as to whether First Nation education counsellors influenced students’ post-secondary program choices. Students perceived themselves to be their greatest influence, while the counsellors felt their influence was greater once students made their program decisions, through encouragement and follow up support. The study raised questions regarding challenges faced by First Nation education counsellors to provide consistent academic, personal and cultural/social supports to their sponsored students. While the study suggested the role of First Nation education counsellors had evolved little from its original financial-administrative role and toward a more rounded offering including interpersonal, academic and cultural supports, in keeping with an educational decolonization process, counsellors face chronic program under funding and are under-staffed. To enhance First Nation students’ academic success, federal and provincial governments and First Nations are encouraged to further support First Nation education counsellors with greater training opportunities (expansion of the Ontario Native Education Counselling Association’s Native Counsellor Training Program), a higher ratio of counsellors to students, and support and promotion of their ability to provide interpersonal and academic counselling. The study challenged First Nation education counsellors to seek more opportunities to maintain consistent engagement with their students, especially with more autonomous or older students. First Nation students were also challenged to seek more from their counsellors than sponsorship. EDD